Management Science, The Journal - Churchman, C. West (Management Science, 1955)
These remarks are concerned with the policies of the journal of the Institute. A journal not only serves as a basis of communication for its time, but also as a monument of effort for some future age. The singularity of the title Management Science dedicates us to the proposition that a science of human administration is a real possibility. Whatever sort of monument our journal may be for the future, its keystone will consist in this conviction.